TYPES AND TECHNOLOGIES OF PERSONALIZED EDUCATION IN THE ERA OF DIGITAL TECHNOLOGIES (Educa Journal of Studies, 2026)
This article presents an opinion on the types of personality-oriented learning, its role in society, the importance and relevance of the use of technology in the XXI-st century in the era of digital technology development.
Keywords: Digital technologies, personality-oriented education, modern education, the XXI-st century.